Gametic cycle and gonadal maturity of Bulimulus bonariensis (Rafinesque, 1833) (Gastropoda: Bulimulidae), in a rural area of Buenos Aires, Argentina - Díaz, Ana Carolina (2023)
Bulimulus bonariensis, a snail distributed over a large part of Argentina, has generated negative effects on the agribusiness. We accordingly conducted a seasonal sampling during 2018–2019 in order to characterize the gametic cycle and establish the size of this gastropod at gonadal maturity. Three reproductive stages were identified: the mature in autumn; the spawn, which begins in winter but occurs mainly in the spring, followed by the post-spawn in summer, where an absence of gonadal rest was evidenced. In the fall, in maturity resorption was observed in addition to abundant primary spermatocytes, secondary spermatocytes, and growing vitellogenic oocytes. At the same time, could correlate the degree of spermioviduct development with the stage of gonadal development. Moreover, we used a logistic regression to calculate the size at gonadal maturity, which was established at the total shell length of 12 mm. In addition, we found that at the beginning of reproductive development those gastropods are protogynous hermaphrodites, but after reaching gonadal maturity became simultaneous hermaphrodites. Finally, B. bonariensis also proved to be an iteroparous species. The information provided here will be essential for delineating and establishing population control strategies.